Anomalous dielectric behaviors of electrolyte solutions confined in graphene oxide nanochannels - Bo Hu (Nature Portfolio, 2021)
Abstract Dielectric behavior of salt aqueous solutions with various concentration in pristine and oxide graphene nanochannels has been investigated by means of molecular dynamic simulations. The motivation in performing this integrated set of simulations was to provide deep insight into the interaction between the size of the enclosure and the oxidation degree of the membrane sheets on the dielectric properties. It was shown that the dielectric permittivity of both aqueous and NaCl solution in confined phase exhibits an anisotropic behavior. The in-plane component decreases with the increase of the concentration of NaCl solution while an increase of the out-of-plane dielectric is observed and these out-of-plane components exhibit a non-monotonous trend and thus exist a critical concentration of NaCl solution with 0.2 mol/L and 0.4 mol/L for both pristine and oxide graphene nanochannels, respectively. This peculiar dielectric behavior results from the addition of ions that significantly perturb the hydrogen bonding network of the confined system, and hence leading to a fluctuation of dipolar of water molecules and dielectric permittivity.